Analisis Double Check Agar Tidak Terjadi Revisi Purchase Order Pada PT. X - Tri Tarisa Dewi; Abdurrahman Faris Indriya Himawan (SEIKO : Journal of Management & Business, 2022)
Abstract The purpose of conducting this research was due to the discovery regarding double check analysis when making a Purchase Order at PT.X, the evidence obtained within the company was that frequent revisions occurred during the Purchase Order process. Delays in the arrival of goods and procurement that is not on schedule result in a production process that is not optimal. Accuracy is needed in making a Purchase Order, so that there is no revision of the Purchase Order, the purchaser must carefully double check when making a Purchase Order so that there is no revision of the Purchase Order. In order to achieve this goal, one way is to establish this policy to make it easier for purchasers and vendors to process Purchase Orders. because the results of doing a double check analysis when making a Purchase Order can affect the effectiveness and efficiency of the Purchase Order process in the company. The motivation for doing an analysis of doing a double check when creating a Purchase Order at PT.X is to better manage the flow of Purchase Orders. If there are frequent revisions to Purchase Orders it causes a lot of risk for the Purchaser in the form of the risk of late arrival of goods, asking for approval from management 2 times, goods that arrive wrong and not as requested. Keywords : purchase order,revision,double check,supply chain